Морфология и габитусные формы легированных бором монокристаллов алмаза при выращивании в системе Fe–Co–Zr - Чепугов, А.П.; Лысаковский, В.В.; Квасница, В.Н.; Ивахненко, С.А.; Заневский, О.А. (Породоразрушающий и металлообрабатывающий инструмент – техника и технология его изготовления и применения, 2010)
The diamond single crystals were synthesized in system based on Fe–Co–Zr with the introduction
of boron-containing compounds in field of diamond thermodinamic stability using the temperature
gradient method. Habitus type and morphology of obtained boron doped diamond single
crystals were studied. It was defined that the distinctive morphology feature of obtained crystals is
the presence of banded surface relief.